The Influence of Social Media on Customer Buying Behavior - Sulfa Sulfia; Refina Dyah Pramesti Utomo Putri; Mutiara Cantika Kamila Putri; Muhammad Alkirom Wildan (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the influence of social media on consumer purchasing behavior using a qualitative approach. Social media has become a primary medium in digital marketing, enabling direct interaction between brands and consumers. This study used an online questionnaire distributed to 50 respondents aged 18–24 years, as well as semi-structured interviews with five informants who had experience shopping through social media. The results showed that attractive visual content, influencer support, and Electronic Word of Mouth (E-WOM) play a significant role in shaping purchasing decisions. This study contributes to the understanding of contemporary marketing practices and offers effective strategies in optimizing social media. Visual content increases product appeal, influencers build consumer trust, and E-WOM serves as a source of information and social validation. These findings provide theoretical contributions to the study of digital consumer behavior and offer practical implications for business actors in designing more effective and relevant social media marketing strategies in the digital era. This study not only enriches the theoretical understanding of consumer behavior in the digital context but also offers practical implications for business actors and marketers. Marketing strategies that emphasize authentic visual elements, collaboration with relevant influencers, and encouraging consumer engagement through online reviews and testimonials have proven effective in influencing purchase intentions. Thus, this study provides an important contribution in the development of social media-based marketing strategies that are more adaptive and responsive to current consumer trends.